2021
DOI: 10.1017/s0373463321000382
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model of vessel trajectory based on generative adversarial network

Abstract: Trajectory prediction is an important support for analysing the vessel motion behaviour, judging the vessel traffic risk and collision avoidance route planning of intelligent ships. To improve the accuracy of trajectory prediction in complex situations, a Generative Adversarial Network with Attention Module and Interaction Module (GAN-AI) is proposed to predict the trajectories of multiple vessels. Firstly, GAN-AI can infer all vessels’ future trajectories simultaneously when in the same local area. Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Artificial neural networks was applied to trajectory prediction using AIS data [25,33,37,38]. Chen et al [7] highlighted the noise issue affecting the quality of AIS data and proposed a method to predict trajectories using neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…Artificial neural networks was applied to trajectory prediction using AIS data [25,33,37,38]. Chen et al [7] highlighted the noise issue affecting the quality of AIS data and proposed a method to predict trajectories using neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…The research was tested on the historical track data of Zhoushan Port. The results showed that compared with seq2seq, GAN and Kalman models, the prediction accuracy of GAN-AI model was improved by 20%, 24% and 72% respectively [10]. Li et al proposed a lane keeping algorithm based on scene analysis to ensure the driver's comfort when driving state changes.…”
Section: Related Workmentioning
confidence: 99%
“…In formula (9), AMX  is the maximum eigenvalue of SN . The consistency test of single level and total level is carried out in MATLAB, and the corresponding weights of environmental factors can be obtained as shown in formula (10).…”
Section: Design Of Intelligent Navigation Obstacle Avoidance Algorithmmentioning
confidence: 99%
“…However, based on the supervised method, the cost of manual annotation is very high and adaptability to new scenarios is not sufficient and must be improved. For this problem, methods based on weak supervised or unsupervised learning [50] are considered, such as the use of generative adversarial network (GAN) to augment the maritime dataset [51].…”
Section: Limitationsmentioning
confidence: 99%